2021
DOI: 10.5121/ijnsa.2021.13202
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of Machine Learning Techniques for DOS Detection in Wireless Sensor Network

Abstract: The nature of Wireless Sensor Networks (WSN) and the widespread of using WSN introduce many security threats and attacks. An effective Intrusion Detection System (IDS) should be used to detect attacks. Detecting such an attack is challenging, especially the detection of Denial of Service (DoS) attacks. Machine learning classification techniques have been used as an approach for DoS detection. This paper conducted an experiment using Waikato Environment for Knowledge Analysis (WEKA)to evaluate the efficiency of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Lama Alsulaiman et al (2021) suggested work conducts an experiment utilizing the Waikato Environment for Knowledge Analysis (WEKA) for assessing the efficacy of five machine learning (ML) techniques for identifying floods, grey holes, black holes, and scheduling DoS attacks on wireless sensor networks. The evaluation depends on the WSN-DS data collection.…”
Section: Literature Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…Lama Alsulaiman et al (2021) suggested work conducts an experiment utilizing the Waikato Environment for Knowledge Analysis (WEKA) for assessing the efficacy of five machine learning (ML) techniques for identifying floods, grey holes, black holes, and scheduling DoS attacks on wireless sensor networks. The evaluation depends on the WSN-DS data collection.…”
Section: Literature Surveymentioning
confidence: 99%
“…The evaluation depends on the WSN-DS data collection. The Random Forest (RF) classifier surpasses conventional methods with 99.72% accuracy [16].…”
Section: Literature Surveymentioning
confidence: 99%
“…Furthermore, spoofing, rotation, and replay attacks jeopardize the integrity of the data. The network is designed on a custom architecture with WSN characteristics, which is the cause of these various attacks [24]. Derives from the network's ad-hoc structure, which includes WSN features.…”
Section: Attacks On the Network Layermentioning
confidence: 99%
“…The dataset for wireless sensor network intrusion detection is referred to as WSN_DS. The dataset represents a variety of denial of service (DoS) attacks, including blackhole, flooding, gray hole, and scheduling attacks, with 19 features and 374,661 records [5,6]. The KDD'99 dataset was created by simulating routine and traffic attacks in a military environment, specifically the US Air Force LAN [4].…”
Section: Introductionmentioning
confidence: 99%